THU0522 Comparison of Cost- Efficacy of Subcutaneous Abatacept Versus Adalimumab in the Treatment of Patients with Rheumatoid Arthritis. (23rd January 2014) - Khanna, D.; Massarotti, E.; Rosenblatt, L.; Budd, D.; Sabater, J.; Hebden, T.
Abstract : Background: Several biologic agents are currently approved to treat adult patients with rheumatoid arthritis (RA). To date, no analyses have compared the cost-efficacy of biologics using data from a head-to-head trial. Objectives: To compare the cost-efficacy of subcutaneous (SC) abatacept (ABA) vs. adalimumab (ADA) using efficacy endpoints from Year 1 of the AMPLE (A batacept Versus Adalim umab Comp arison in Biol ogic Naive RA Subjects with Background Methotrexate) trial, the first head-to-head trial of biologics in RA patients with an inadequate response to methotrexate (MTX). Methods: AMPLE is a phase IIIb, non-inferiority trial, comparing the efficacy of ABA vs. ADA in adults with RA for ≤ 5 years diagnosed with moderate to high disease as defined by DAS28-CRP (≥ 3.2) at screening, despite treatment with MTX (at least 15 mg/wk). A cost-efficacy analysis determined the cost per patient achieving several clinical and patient-reported outcomes (PRO) over 1 year. Efficacy data including ACR responses (ACR20, ACR50, and ACR70), remission [DAS28<2.6], improvements in physical function [defined as a reduction in HAQ-DI score of ≥ 0.3 units] and improvements in activity limitation [captured using the Activity Limitation Questionnaire, which assesses the time over the previous 30 days that a patient had limitations in performing work or non-work activities] were used for this analysis. The annual cost of therapy of ABA (125 mg weekly) and ADA (40 mg biweekly) was based on the approved net costs per unit dose in the United States (in dollars) and Germany (statutory health insurance (GKV) perspective in a retail setting considered, in Euros) multiplied by frequency of administration per dose. Cost of MTX was not included in the calculation because it was assumed to be the same for both treatments. Results: The cost-efficacy ratio between ABA and ADA for all ACR response rates was comparable (Only ACR50 responses shown in Table, in US Dollars and Euros). Other outcomes that were comparable at 1 year included: cost per remission [95% CI] (ABA: (63, 282, [55, 807-73, 265]); 39, 649€ [34, 965€-45, 903€] ADA: 67, 947 [59, 436-79, 083]); 47, 098€ [41, 198€-54, 817€], cost per HAQ response (ABA: 45, 366 [41, 643−49, 820]; 28, 424€ [26, 091€-31, 214€] ADA: 49, 947 [45, 625−55, 067]; 34, 621€ [31, 625-38, 170€]), and cost per day gained without activity limitation (323 [287−369]; 202€ [180€-231€] and 380 [333−442]; 263€[231€-307€] respectively). Conclusions: The cost-efficacy of ABA versus ADA is comparable in adult RA patients, both in the United States and Europe, based on measures of clinical efficacy and patient-reported outcomes from the AMPLE trial. Disclosure of Interest: D. Khanna Consultant for: Bristol-Myers Squibb, E. Massarotti Grant/research support from: Bristol-Myers Squibb, Consultant for: UCB, L. Rosenblatt Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, D. Budd Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, J. Sabater Employee of: Bristol-Myers Squibb, T. Hebden Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb